Mrs. Toggle's beautiful blue shoe - Pulver, Robin; Alley, R. W. (Robert W.) (New York : Four Winds Press ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1994)
Mrs. Toggle joins the children in a game of kickball and loses her beautiful blue shoe.
Sequel to: Mrs. Toggle and the dinosaur. c1991.
School Library Journal
Book Links (A.L.A.)
Booklist
3.1
K-3
Keywords: Teachers -- Fiction; Schools -- Fiction; Humorous stories; Teachers -- Fiction; School stories; Humorous fiction